2018
DOI: 10.1136/bcr-2017-223154
|View full text |Cite
|
Sign up to set email alerts
|

Isolated bladder schwannoma: a rare presentation

Abstract: Bladder schwannoma is a rare tumour arising from Schwann cells in nerve sheaths. It is usually more common in patients diagnosed with neurofibromatosis. However, isolated cases of urinary bladder schwannoma is incredibly rare, attributing to <0.1% of bladder tumours. A literature review and analysis revealed that it presents in adulthood, is mostly symptomatic and diagnosis is established histologically. We report a case of isolated bladder schwannoma in 25 year-old female who presented with dyspareunia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Surgical resection is the main method of treatment. The methods include partial cystectomy [ 4 , 7 – 9 , 12 ] and TURBT [ 3 , 10 , 11 , 17 , 18 ]. All of the cases reported for partial cystectomy are open, except for a case report of laparoscopic partial cystectomy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the main method of treatment. The methods include partial cystectomy [ 4 , 7 – 9 , 12 ] and TURBT [ 3 , 10 , 11 , 17 , 18 ]. All of the cases reported for partial cystectomy are open, except for a case report of laparoscopic partial cystectomy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jallad et al revealed only 14 other reported cases of isolated bladder schwannoma. 4 In 13 out of the 14 cases of isolated bladder schwannoma, the mode of presentation was clearly described, of which, the majority was symptomatic and presented with lower urinary tract symptoms (45%), hematuria (45%), pelvic pain (10%), recurrent urinary tract infections (10%), and/or dyspareunia (10%). In our case, the disease was revealed incidentally.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, bladder interstitial tumor is relatively rare. Primary bladder schwannomas accounts for 0.1% of all bladder tumors ( 2 ). Schwannomas remain the most common ones in the head and neck (40–50%) ( 3 ), which could appear anywhere in the body where nerve sheath exists.…”
Section: Introductionmentioning
confidence: 99%